An assessment of employment equity within the Safety and Security Directorate: case study of a municipality in the Western Cape - Petersen, Franquin (University of the Western Cape, 2015)
Masters in Public Administration - MPA === This research assesses the challenges faced by a diverse group of employees within the Safety and Security Directorate in a Municipality in the Western Cape, which is a service organisation. The manner in which Employment Equity (EE) is introduced and controlled in this organisation can have a great influence on the staff. Experts agree that there are many arguments in favour and against Employment Equity, making it a formidable and difficult task for any management team (Grogan, Stelzer, Jordaan & Maserumele, and 2005:94). It is imperative to grasp the understanding of staff and management on EE and other related issues to measure if any progress was made and how to perhaps improve on current employment equity related practices in the organisation. The research method comprises both the quantitative and qualitative methodology in the form of a questionnaire survey and a sample of the research population. The research revealed that although much progress has been made with employment equity in general, there are many challenges in this Municipality in the Western Cape. Specific recommendations are made to address these challenges. For further research, it is recommended that employment equity be investigated holistically in every department and directorate.